Los alcornocales andaluces: regeneracion y REPOBLACION ARTIFICIAL - Sánchez García, J. M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
After a brief description of the types of cork tree groves that exist in Andalusia, a succint review of the way and necessary conditions in wich the restocking is done at present. Also data referring to the reforestation with Quercus suber in the last decade are collected. Finally a view of the place that the cork oak takes in the framework of the Andalusian Forestry Plan.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Andalusian Forestry Plan; Cork Oak Forest; Reforestation; Restocking